2022
DOI: 10.1172/jci161566
|View full text |Cite
|
Sign up to set email alerts
|

A SARM1-mitochondrial feedback loop drives neuropathogenesis in a Charcot-Marie-Tooth disease type 2A rat model

Abstract: Conflict-of-interest statement A.D. and J.M. were cofounders, of Disarm Therapeutics, a wholly owned subsidiary of Eli Lilly & Company. A.J.B. and Y.S. consulted for Disarm Therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 76 publications
1
21
0
Order By: Relevance
“…47,48 However, it has had mixed effectiveness in preventing secondary axon degeneration in models of different variants of genetic demyelinating neuropathies. 49,50 We have previously shown that in our model of primary axonal injury, use of WLD s mice, which also show delayed Wallerian degeneration, did not protect from axonal injury. 51 This has also been demonstrated in SARM1 KO mice in our primary axonal injury model (unpublished observations).…”
Section: Secondary Axon Degeneration Is Prevented By Axonal Calpain I...mentioning
confidence: 73%
See 1 more Smart Citation
“…47,48 However, it has had mixed effectiveness in preventing secondary axon degeneration in models of different variants of genetic demyelinating neuropathies. 49,50 We have previously shown that in our model of primary axonal injury, use of WLD s mice, which also show delayed Wallerian degeneration, did not protect from axonal injury. 51 This has also been demonstrated in SARM1 KO mice in our primary axonal injury model (unpublished observations).…”
Section: Secondary Axon Degeneration Is Prevented By Axonal Calpain I...mentioning
confidence: 73%
“…Deletion of the SARM1 protein has been shown to protect against axon degeneration in many peripheral neuropathy models, including chemotherapy‐induced peripheral neuropathies, diabetic neuropathies as well as central nervous system models of demyelinating disease 47,48 . However, it has had mixed effectiveness in preventing secondary axon degeneration in models of different variants of genetic demyelinating neuropathies 49,50 . We have previously shown that in our model of primary axonal injury, use of WLD s mice, which also show delayed Wallerian degeneration, did not protect from axonal injury 51 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the initial mitochondrial defects due to the MFN2 mutation lead to SARM1 activation that in turn feeds back on the mitochondria to worsen their pathology. 23 This exciting work identifies SARM1 as a potent target for CMT2A but also for other neurodegenerative conditions with significant mitochondrial involvement and warrants further investigations on the role of SARM1 in other forms of CMT2 but also in models of CMT1 with more extensive secondary axonal degeneration. Currently, great efforts are devoted to developing SARM1 inhibitors and recently a potent and selective small molecule isoquinoline inhibitor of SARM1…”
Section: Sarm 1 Inactivation To Prevent Axonal Degeneration In Cmt2mentioning
confidence: 84%
“…In the Mfn2 H361Y rat, a model that recapitulates several hallmarks of the human disease, such as progressive dying back axonal degeneration, muscle atrophy, neuromuscular junction (NMJ) abnormalities and mitochondrial defects, deletion of Sarm1 rescued the axonal, synaptic, muscle and functional phenotypes, indicating that SARM1 is directly responsible for most of the pathological findings. 23 Interestingly, also some of the mitochondrial abnormalities were rescued in these mice after Sarm1 deletion, despite the presence of the mutant MFN2. This suggests that the initial mitochondrial defects due to the MFN2 mutation lead to SARM1 activation that in turn feeds back on the mitochondria to worsen their pathology.…”
Section: Sarm 1 Inactivation To Prevent Axonal Degeneration In Cmt2mentioning
confidence: 86%
See 1 more Smart Citation